Prevalence of functional disability and associated factors in brazilian elderly (Research, Society and Development, 2022)
The present study aimed to estimate the prevalence of functional disability (FD) in instrumental activities of daily living (IADLs) and associated factors in elderly Brazilians. This is a cross-sectional study, with a sample of elderly people of both sexes, from the National Health Survey (NHS), 2013. Descriptive statistics and the chi-square test were used, considering statistically significant associations for p < 0,05, and using the SPSS program (version 22). It was observed that the prevalence of FD in IADLs was 17.3%. The factors associated with FD were: age (p